UJI STABILITAS SEDIAAN AMPISILLIN SULBAKTAM SETELAH REKONSTITUSI - I Gede Edy Sagitha; Suharjono Suharjono; Yulistiani Yulistiani; Isnaeni Isnaeni (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2023)
Repeated use of antibiotic ampicillin sulbactam after reconstitution, therefore in storage various many factor can affect it stability such as type of solvent used, storage temperature and storage time. Objective of study is to analyze the chemical stability product of ampicillin sulbactam in repeated use with the parameters of the solvent and storage temperature Sample products were weighed and reconstituted using WFI and NS solvents, diluted ad 20 ppm and put into sterile vials. Then stored at room temperature (25-30 ° C) and refrigerator temperature (4-8 ° C). Storage is carried out for 24 hours which is divided into 4 -time series, namely 0, 1, 4 and 24 hours. Each time series is microbiological tested and after 18 hours incubation the inhibition zone is observed and its diameter measured using calipers. Result of study is at 0th hour showed a significant difference in different solvents. Samples dissolved with NS solvents have a greater inhibition zone than those dissolved using WFI. This happens because there is a primary salt effect that occurs with the influence of electrolytes (salt) or variations in the strength of ions can affect the coefficient of activity that affects the reaction rate. From the statistical analysis at the 1st and 4th hours, the storage temperature that provides significant result, storage in the refrigerator produces better results compared to storage at room temperature. At 24 hours the temperature and solvent did not give the significant result on the stability of the sulbactam ampicillin sample. Conclusion is NS solvents give better results than WFI solvents. Samples are more stable if stored in a refrigerator. After 4 hours based on the above study the sample no longer meets the requirements of Indonesian Pharmacopoeia 5th edition